Role of the ventral striatum in developing anorexia nervosa - Fladung, A-K (Nature Publishing Group, 2013)
Functional imaging data in adult patients with anorexia nervosa (AN) support a dysfunctional signal in the ventral striatum as neural signature of AN. In the present study, development of this signal was investigated with the prediction that a characteristic pattern of ventral–striatal signalling will be shown in response to cues associated with food restriction that reflects the evolvement of starvation dependence over time. The signal was assessed in adolescent patients with AN, whose duration of illness was about five times shorter relative to the adult sample. During functional magnetic resonance imaging subjects were required to estimate weights of body images (underweight, normal weight, overweight) and to process each stimulus in a self-referring way. Relative to age-matched, young healthy controls, underweight stimuli were already associated with greater activity of the ventral striatum, and processing of normal-weight stimuli elicited already reduced signalling. Subjective preferences showed exactly the same pattern of results. Relative to adult AN, the present data reveal a developing dysfunctional signal that, if untreated, will essentially contribute to the maintenance of AN. We discuss putative mechanisms that may play a crucial role in the development of AN, and also deduce new hypotheses about the involvement of the midbrain dopamine system, of which illness-related alterations may contribute to the development of AN.